Empirical modeling of micromechanical bending process of vertically aligned carbon nanotube forest using response surface methodology. Issue 1 (1st January 2017) - Masud Rana, M.; Saleh, T.; Mohd Asyraf, M.R.; Muthalif, Asan G.A.
Abstract: Micromechanical bending (M2B) is a newly developed micro patterning technique applied for vertically aligned carbon nanotubes (VACNTs) array, commonly known as CNT forest. This process is required to realize the various use of CNT forest in Micro-Electromechanical Systems (MEMS). There are various parameters involved in M2B process that controls the surface roughness of the processed structure of the CNT forest. However, there is no mathematical model available, yet that could predict the influence of these parameters on the surface roughness of the patterned CNT forest. In this paper, an empirical approach has been used to predict the surface roughness for the micromechanical bending (M2B) processed CNT forest. At first, several experiments were conducted by varying different process parameters such as tool rotational speed, lateral speed and a step size of the bend. Best optimized process parameters were identified at 2, 000 rpm tool rotational speed, 1 mm/min lateral speed and 1 μm step size that produced a minimum surface roughness of Ra = 15 nm. Finally, a response surface methodology (RSM) based mathematical model was developed and validated with reasonable accuracy to understand the impact of different parameters on the M2B process.